MRI and CT of the cardiovascular system - Higgins, Charles B.; Roos, Albert de, 1953- (Wolters Kluwer Health / Lippincott Williams & Wilkins, 2013)
Leave no disease undetected with MRI and CT of the Cardiovascular System, your definitive guide to magnetic resonance and computed tomography for cardiovascular health. Authored by a collaboration of international experts, this vivid, four-color third edition imparts the latest technologies in a rapidly advancing field. With topics that range from anatomy, to MR in infants and children, to risk assessment in ischemic heart disease this text includes seven new chapters to reflect the rising tide of technological discovery as it pertains to cardiology. Thanks to its expert analysis, procedural g.